Free Legal Aid Policy: The Role and Challenges of Legal Aid Organizations to the Poor - Baried, Rizky Ramadhan (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
The Ministry of Law and Human Rights of the Republic of Indonesia makes a policy for legal aid organizations to carry out legal aid on a pro bono basis to get the legal aid budget ceiling for the following year. The purposes of this study are to analyze the role of legal aid organizations in realizing pro bono legal aid to implement access to justice for the poor; and to analyze their challenges in fulfilling The Ministry of Law and Human Right’s policy of implementing pro bono legal aid to get the legal aid budget ceiling for the following year. This research using empirical juridical research methods, with a sociological, statutory and a conceptual approach. Primary and secondary data obtained through interview techniques, observations, and literature studies, then analyzed qualitatively. The results of this study show that legal aid organizations play a preventive role in the form of legal counseling activities to the community and actively serve consultations to legal aid both inside and outside the trial for the poor; The challenge they encountered was in the form of rivalry between fellow legal aid organizations which were then required to innovatively get closer to the need for free legal aid for the underprivileged.